#ShareTheRoadWithHer evaluating women’s landscape preference of cycling infrastructure In Quezon City based on mobility needs - Fajardo, Joselle Marie B.
The world has been historically built for men. This manifests in how our built environment is designed, as the gender gap in cycling is prevailing due to the lack of cycling infrastructure that match women's preferences and mobility needs. There are two main themes in cycling and gender studies: 1) women cycle less because they have greater safety concerns due to issues of street harassment, and 2) women have more complex mobility patterns due to juggling household tasks and care responsibilities. While there has been convergence with men's and women's activities in the past decades, gender-specific needs have to be addressed. Failing to recognize these differences hampers the development of achieving transport equity. This study aims to create planning solutions to encourage women to cycle by designing an ideal cycling condition anchored on women’s mobility needs. In the results, it is reflected that there is a difference between men and women’s mobility patterns, and current cycling infrastructure do not match demands on mobility needs. Thus, three planning schemes were developed based on design principles on mobility patterns and safety perception. The optimum design intervention has received the highest rating among the three planning schemes. Thus, the planning solutions and policy interventions created in this study is anchored on the scenario that the Philippines has veered away from car-centrism. A chosen route in Quezon City is used as a pilot site in applying the women-specific interventions and policy solutions. By closely examining the experiences and preferences of women, we can provide alternative solutions and interventions to create safer and more inclusive streets.